Warriors and Chief - G.F. MacDonald (1979)
Re-enactment of the story of 'Nekt, the warrior chief from Gitwangak who built and defended the site known as battle hill. The story takes place at 'Battle Hill near Gitwangak village. 'Nekt was an aggressive warrior and led many successful raids against neighbouring tribes. He is remembered and celebrated by the Gitxsan people as a powerful and great leader.